Reconstruction of Beef Cattle and Dairy Cattle Development in Indonesia - Abdulrahman Siregar; Abdurrays Ambar Karto (Indonesian Center for Animal Research and Development, 1999)
Dairy cattle and beef cattle industrial development have not fulfilled consumption requirement in Indonesia. Indonesia has imported milk since the beginning of Pelita I (Five years planning of Indonesian development). Once Indonesia was able to export beef, but a now days beefis being imported, and continue to increase every year. There are four factors need to be considered (1) the dairy and beef cattle form which has been raised separately, should be raised jointly and developed with